PENGARUH RESHUFFLE KABINET KERJA DAN PELUNCURAN PAKET KEBIJAKAN EKONOMI (JILID IâJILID VIII) TERHADAP INDEKS HARGA SAHAM GABUNGAN DI BURSA EFEK INDONESIA TAHUN 2015 - Anggrahin, Puspa; Setyawanti, Dandang (KIAT BISNIS, 2016)
The purpose of this research is to find out the average differentation of JCI before and after reshuffle of the Working Cabinet and the launching of the Economic Policy Package Volume I- Volume VIII. This research based on the secondary data wich was published by IDX. The data used in this research is from JCI in the closing price daily. The research method used is event study with event period for 7 days. The significance average level of JCI will be tested with T Test. The result of this research shows the average differetation of JCI before and after events reshuffle of the Working Cabinet, the launching of the Economic Policy Package Volume III, Volume V,Volume VII. Keyword: reshuffle of the Working Cabinet, Economic Policy Package, JCI